Whole genome sequence and phenotypic characterization of a Cbm+ serotype e strain of Streptococcus mutans. (17th April 2018) - Avilés‐Reyes, A.; Freires, I. A.; Kajfasz, J.K.; Barbieri, D.; Miller, J.H.; Lemos, J.A.; Abranches, J.
Summary: We report the whole genome sequence of the serotype e Cbm + strain LAR01 of Streptococcus mutans, a dental pathogen frequently associated with extra‐oral infections. The LAR01 genome is a single circular chromosome of 2.1 Mb with a GC content of 36.96%. The genome contains 15 phosphotransferase system gene clusters, seven cell wall‐anchored (LPxTG) proteins, all genes required for the development of natural competence and genes coding for mutacins VI and K8. Interestingly, the cbm gene is genetically linked to a putative type VII secretion system that has been found in Mycobacteria and few other Gram‐positive bacteria. When compared with the UA159 type strain, phenotypic characterization of LAR01 revealed increased biofilm formation in the presence of either glucose or sucrose but similar abilities to withstand acid and oxidative stresses. LAR01 was unable to inhibit the growth of Strpetococcus gordonii, which is consistent with the genomic data that indicate absence of mutacins that can kill mitis streptococci. On the other hand, LAR01 effectively inhibited growth of other S. mutans strains, suggesting that it may be specialized to outcompete strains from its own species. In vitro and in vivo studies using mutational and heterologous expression approaches revealed that Cbm is a virulence factor of S. mutans by mediating binding to extracellular matrix proteins and intracellular invasion. Collectively, the whole genome sequence analysis and phenotypic characterization of LAR01 provides new insights on the virulence properties of S. mutans and grants further opportunities to understand the genomic fluidity of this important human pathogen.